ANALISIS MISKONSEPSI SISWA SEKOLAH DASAR PADA MATERI ILMU PENGETAHUAN ALAM - Aryani Nova Rossydah; Citra Septyani Zuhrotunnisa; Deana Pinkan; Sri Darsini, Eka Septiana Nakiya Khusna; Nazilatun Nisa; Putri Amelia; Rahmahtiawati Marfiyannur Rahmandita; Wati Sukmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Understanding the idea of MISCONCEPTION in the context of teaching natural sciences (IPA) in elementary schools is the main goal of this article. Understanding the idea understanding strategies employed by Natural Science (IPA) instructors and the challenges faced during the Merdeka Belajar curriculum's implementation are the goals of this essay. This study employed a qualitative approach using a descriptive methodology. A case study was employed as the data gathering method, in which the researcher thoroughly explains and examines the issue until particular outcomes are achieved. Teachers, pupils, and the principal of primary schools are the subjects of this study. Books, journals, and scientific articles are examples of secondary data sources that are used in this article. Descriptive-analytical analysis, which incorporates critical analysis, critical interpretation, and conclusion drawing, was employed to examine the data. Teachers employ a variety of assessment techniques, according to the study's findings. They employ assignments, written exams, and oral exams to evaluate cognitive abilities. Journals, observations, and self-evaluations are used in the affective component.